PERILAKU BIAYA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA CAFE & RESTO KOPI KERETA API SENA - Devica Natali Tambunan; Geo Fanny Cantika Aritonang; Citra Nadya Siregar (STKIP Subang, 2026)
The objectives of this study are: (1) To determine the influence of cost behavior on employee performance at Sena Train Coffee Cafe & Restaurant; (2) To determine the influence of the work environment on employee performance; (3) To determine the simultaneous influence of cost behavior and work environment on employee performance. This research uses a quantitative approach with field study and literature review methods. Primary and secondary data were collected through questionnaires from 25 respondents (sample) out of 80 total employees. Data were analyzed using multiple linear regression in SPSS. Results show: (1) Cost behavior significantly influences employee performance (t = 2.635, sig = 0.010); (2) Work environment significantly influences employee performance (t = 2.593, sig = 0.011); (3) Both variables simultaneously influence employee performance (F = 9.802, sig = 0.000). The coefficient of determination (Adjusted R²) is 0.177, meaning both variables explain 17.7% of the variance in employee performance.